Comparison of the burden of self-reported bacterial sexually transmitted infections among men having sex with men across 68 countries on four continents - Ulrich Marcus; Maria Veras; Jordi Casabona; Carlos F. Caceres; Nathan Lachowsky; Susanne B. Schink; Axel J. Schmidt (BMC Public Health, 2023)
Abstract Background Men who have sex with men (MSM) are in general more vulnerable to sexually transmitted infections (STIs) than the heterosexual men population. However, surveillance data on STI diagnoses lack comparability across countries due to differential identification of MSM, diagnostic standards and methods, and screening guidelines for asymptomatic infections. Methods We compared self-reported overall diagnostic rates for syphilis, gonorrhea, and chlamydia infections, and diagnostic rates for infections that were classified to be symptomatic in the previous 12 months from two online surveys. They had a shared methodology, were conducted in 68 countries across four continents between October 2017 and May 2018 and had 202,013 participants. Results Using multivariable multilevel regression analysis, we identified age, settlement size, number of sexual partners, condom use for anal intercourse, testing frequency, sampling rectal mucosa for extragenital testing, HIV diagnosis, and pre-exposure prophylaxis use as individual-level explanatory variables. The national proportions of respondents screened and diagnosed who notified some or all of their sexual partners were used as country-level explanatory variables. Combined, these factors helped to explain differences in self-reported diagnosis rates between countries. The following differences were not explained by the above factors: self-reported syphilis diagnoses were higher in Latin America compared with Europe, Canada, Israel, Lebanon, and the Philippines (aORs 2.30 – 3.71 for symptomatic syphilis compared to Central-West Europe); self-reported gonorrhea diagnoses were lower in Eastern Europe and in Latin America compared with all other regions (aORs 0.17-0.55 and 0.34 - 0.62 for symptomatic gonorrhea compared to Central-West Europe); and self-reported chlamydia diagnoses were lower in Central East and Southeast Europe, South and Central America, and the Philippines (aORs 0.25 - 0.39 for symptomatic chlamydia for Latin American subregions compared to Central West Europe). Conclusions Possible reasons for differences in self-reported STI diagnosis prevalence likely include different background prevalence for syphilis and syndromic management without proper diagnosis, and different diagnostic approaches for gonorrhea and chlamydia.